Capitalist Crisis, Communication, & Culture – Introduction to the Special Issue of tripleC - Christian Fuchs; Matthias Schafranek; David Hakken; Marcus Breen (tripleC: Communication, Capitalism & Critique)
The worldwide economic downturn is indicative for a new large crisis of capitalism. The future of capitalism is in this situation not determined, but depends on collective human agency. This introduction to the special issue of tripleC on “Capitalist Crisis, Communication & Culture” presents general arguments about the crisis, a general model of the political economy of capitalist communication, and a systematic typology of literature about capitalist crisis & communication. The introduced model of the political economy of capitalist communication is comprised of seven interconnected moments: 1) the media content industry, 2) the media infrastructure industry, 3) the interaction of the media economy and the non-media economy, 4) the interaction of the finance sector and the media economy, 5) alternative media, 6) media reception, 7) media prosumption. The model is used for classifying actual and potential research about the communicative dimension of the new capitalist crisis.